Combination therapy for postinflammatory hyperpigmentation: A systematic review - Rini Tri Utari (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2025)
Background: Post-inflammatory hyperpigmentation (PIH) poses a considerable dermatological concern, affecting individuals of various ethnic backgrounds, with a notably higher prevalence among those with darker skin tones. The intricate pathophysiology of PIH, which involves inflammatory mediators and melanogenic pathways, necessitates a multifaceted treatment approach to achieve the best possible clinical results. Purpose: This systematic review evaluates the effectiveness, safety, and clinical outcomes of various combination therapies for managing post-inflammatory hyperpigmentation (PIH), with a focus on their synergistic effects and suitability for diverse skin types. Method: A systematic review with article selection guided by the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The systematic review process begins with the formulation of clinical questions relevant to the topic. Before this, the authors establish PICOS criteria, which stand for: P (problem, patient, or population), I (intervention, prognostic factor, or exposure), C (comparison or control), O (outcome), and S (study design). For this article, P: Individuals of any age and skin type diagnosed with post-inflammatory hyperpigmentation (PIH), I: Any combination therapy involving two or more active ingredients or treatment methods, C: Single therapy, alternative combination therapies, or placebo, O: Clinical improvement in PIH, patient satisfaction, adverse effects, and treatment duration, S: Randomized controlled trials. The article search was conducted systematically using the keywords: “post-inflammatory hyperpigmentation” AND “combination therapy” AND “hyperpigmentation treatment” AND “topical therapy” AND “skin pigmentation” AND “melanin” AND “tyrosinase inhibitors” AND “retinoids” AND “kojic acid” AND “hydroquinone” AND “tranexamic acid” AND “niacinamide” AND “Boolean operators”. Results: The review of eight studies found that combination therapies were more effective than monotherapy for treating post-inflammatory hyperpigmentation (PIH). Dual treatments, such as glycolic acid cream with peeling and TCA with PRP, showed notable improvements. Combining chemical peels with topical agents was especially effective for stubborn cases. Success depended on proper patient selection, personalized plans, and timing. Overall, targeting multiple pigmentation pathways improved outcomes and was safe, particularly for darker skin types (Fitzpatrick IV–VI). Conclusion: Combination therapy is the most effective approach for treating PIH, as it utilizes synergistic treatment methods tailored to individual patient factors like skin type and PIH severity.